Effect of static and dynamic jaw positions on postural stability among people with blindness. Issue 9 (2nd August 2022) - Alghadir, Ahmad H.; Zafar, Hamayun; Ahmed Iqbal, Zaheen; Anwer, Shahnawaz; Iqbal, Amir
Abstract: Background: In comparison with the people with normal sight, the mean center of gravity (COG) velocity is significantly higher among blind people. A strong relationship has been shown between jaw and neck sensorimotor and postural control. The purpose of this study was to determine the effect of different static and dynamic jaw positions on postural stability among subjects with blindness. Methods: Postural stability was measured as COG velocity in 39 blind subjects under the following five conditions: resting jaw (natural jaw position with no instructions, control), open jaw (teeth of both jaws slightly apart), clenched jaw (teeth tightly closed across each other), chewing (a standard bolus of gum at the natural palace), and tongue position (positioned behind the upper incisors) while standing on firm and foam surfaces. Results: The mean COG velocity while standing on the firm surface during resting, open jaw position, clenched jaw position, chewing, and tongue positions were 0.54, 0.50, 0.44, 0.59, and 0.46 deg/s, respectively. The mean COG velocity while standing on the foam surface during resting, open jaw position, clenched jaw position, chewing, and tongue positions were 1.42, 1.23, 1.10, 1.14, and 1.06 deg/s, respectively. Compared to the firm surface, the COG velocity was significantly higher on the foam surface in all five conditions ( p  < .001). In the comparison between the conditions, there were no significant differences in either the firm or foam surface in all five conditions ( p  > .05). Conclusion: People with blindness behave in the same way as sighted subjects on firm and foam surfaces. However, changes in static and dynamic jaw positions do not affect postural stability among them.